Impact of Equity Liquidity on Corporate Value—— Based on The Empirical Analysis of China’s A-Share Listed Companies - Zhang, Ruixin (Transactions on Economics, Business and Management Research, 2024)
Since the establishment of the Shanghai and Shenzhen Stock Exchange, China’s stock market has experienced a development process from scratch, from small to large, and from weak to strong. During this period, the liquidity of China’s stock market has increased significantly. The stock market can affect the real economy by changing the motivation and influencing the behavior of enterprises, which is crucial to economic development. Many scholars at home and abroad have studied the impact of stock liquidity on enterprise value from different perspectives. This paper finds that the stock liquidity has a significant positive impact on the value of enterprises. The higher the level of stock liquidity, the higher the enterprise value, and the company’s equity structure can play a role as an intermediary variable in the process of stock liquidity affecting the enterprise value.